2018
DOI: 10.1148/radiol.2017170365
|View full text |Cite
|
Sign up to set email alerts
|

Focal Liver Lesions: Computer-aided Diagnosis by Using Contrast-enhanced US Cine Recordings

Abstract: Purpose To assess the performance of computer-aided diagnosis (CAD) systems and to determine the dominant ultrasonographic (US) features when classifying benign versus malignant focal liver lesions (FLLs) by using contrast material-enhanced US cine clips. Materials and Methods One hundred six US data sets in all subjects enrolled by three centers from a multicenter trial that included 54 malignant, 51 benign, and one indeterminate FLL were retrospectively analyzed. The 105 benign or malignant lesions were conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Ultrasonography is useful for the diagnosis of hepatic focal lesions, which is based on their distinctive echogenicities-the grayscale morphologic features. The development of ultrasound contrast agents provided us with more information about tissue perfusion and helped to improve diagnostic accuracy, particularly in focal liver lesions (FLLs) [15][16][17] . Compared with first-generation agents, the second-generation ultrasound contrast agent SonoVue consisting of sulfur hexafluoride microbubbles (Bracco, Milan, Italy) has a high flexibility shell and is more stable to acoustic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is useful for the diagnosis of hepatic focal lesions, which is based on their distinctive echogenicities-the grayscale morphologic features. The development of ultrasound contrast agents provided us with more information about tissue perfusion and helped to improve diagnostic accuracy, particularly in focal liver lesions (FLLs) [15][16][17] . Compared with first-generation agents, the second-generation ultrasound contrast agent SonoVue consisting of sulfur hexafluoride microbubbles (Bracco, Milan, Italy) has a high flexibility shell and is more stable to acoustic pressure.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 For AI‐US, our study reported the largest sample size with an independent test dataset. 32 , 33 , 34 Compared with a previous AI‐US study with an independent test dataset, 35 our AI model exhibited better performance (AUC: 93.4% vs 88.1%).…”
Section: Discussionmentioning
confidence: 58%
“…Its performance was comparable with or even better than the previously reported performance of non‐AI CT (Se: 89%, Sp: 94%) and MR (Se: 83%, Sp: 75%). 7 A CEUS‐based AI model was also reported in a recent study of FLL differentiation 34 ; however, that study used machine learning algorithms based on manually extracted features for model development. That study reported an Se of 83.3% and an Sp of 62.7%, and these values are lower than those obtained with our deep learning model.…”
Section: Discussionmentioning
confidence: 99%
“…Several proposed practical algorithms for the clinical use of MPUS in chronic liver disease and FLL are available [ 24 ], and computer-aided diagnosis systems were conceived based on the new US features [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%